MOTIVASI BELAJAR SISWA DISLEKSIA DALAM MENGATASI KESULITAN BELAJAR - Sitta Novia Muyassaroh; Izzatin Kamala (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Children with special needs (ABK) who have dyslexia can cause children to have difficulties in learning, including difficulties in spelling, reading, writing and communicating with others. The subjects in this study were dyslexic students with the initials DH at one of the Inclusive Elementary Schools in Sleman. The results showed that parents only realized dyslexic children when the children entered their teens, the environment also affects the learning motivation of dyslexic children, and the efforts made by teachers and parents in overcoming the learning difficulties of dyslexic students. From the results of the study, DH experienced dyslexia in the form of difficulty in speaking, hesitation when answering the interlocutor's questions, spelling word for word slowly with a soft or low voice or intonation, and difficulties in writing and difficulty communicating with the surrounding environment. The method used in this research is descriptive qualitative. Data collection techniques were carried out by in-depth interviews, observation and literature review. By providing maximum learning assistance between teachers and parents, it will increase learning motivation for dyslexic children.